2019
DOI: 10.11110/kjpt.2019.49.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Two new generic records in the orchid flora of Myanmar

Abstract: The species diversity of Orchidaceae is believed to be extremely high in Myanmar. Like in other plant groups, little basic inventory work has been done thus far. During floristic surveys conducted in Popa Mountain Park (Mandalay Region), Natma Taung National Park (Chin State), and in the Ywangan area (southwestern Shan State), we encountered two interesting orchid species which were determined to be new generic records in the flora of Myanmar. Thuniopsis cleistogama was previously considered endemic to Yunnan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In addition to its significant genetic divergence, several studies have suggested that Thuniopsis exhibits unique morphological features that differentiate it from other members of Coelogyninae ( Li et al, 2015 ; Kang et al, 2019 ; Kurzweil et al, 2020 ). Thuniopsis is superficially similar to Thunia in the elongate leafy stem, carrying distichous, soft and plicate leaves, but can be easily distinguished from the latter by having prominent subterranean corms; much smaller and spurless flowers; prominent stigma and bilobed rostellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its significant genetic divergence, several studies have suggested that Thuniopsis exhibits unique morphological features that differentiate it from other members of Coelogyninae ( Li et al, 2015 ; Kang et al, 2019 ; Kurzweil et al, 2020 ). Thuniopsis is superficially similar to Thunia in the elongate leafy stem, carrying distichous, soft and plicate leaves, but can be easily distinguished from the latter by having prominent subterranean corms; much smaller and spurless flowers; prominent stigma and bilobed rostellum.…”
Section: Discussionmentioning
confidence: 99%
“…f., this species has originally assigned to the member of that genus ( Xu et al, 2010 ). Recently it was considered to be congeneric with a long-lost and rediscovered species in Myanmar formerly classified in the genus Arundina or Dilochia ( Kang et al, 2019 ; Kurzweil et al, 2020 ). Owing to remarkable vegetative similarity in morphology, the species has long been mistakenly identified as a member of other genera for over 100 years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some literature provides information on specimens from Myanmar that can be cited as specimen-based species occurrences in Myanmar (Kurzweil and Lwin 2015, Tanaka et al 2015, Watthana et al 2015, Aung et al 2017, Jin and Kyaw 2017, Yang et al 2017, Kurzweil and Ormerod 2018, Ding et al 2019, Kang et al 2019, Mu et al 2019, Ya et al 2019.…”
Section: Investigation Of Herbarium Specimensmentioning
confidence: 99%
“…As for taxonomic status, we followed the updated classification of Orchidaceae (Chase et al 2015) and all relevant papers of orchid taxonomy and systematics (Pridgeon et al 2001, 2005, Chen et al 2009, Gardiner 2012, Gardiner et al 2013, Jin et al 2014, Vermeulen et al 2014, Raskoti et al 2016, Raskoti et al 2017, Govaerts 2018, Ng et al 2018. In addition, all papers of new species descriptions and new records of Myanmar orchid flora were reviewed to identify the species occurrences and distribution in Myanmar , Roberts et al 2008, Chen et al 2009, Tanaka et al 2010, Ormerod 2012, Pedersen et al 2011, Kurzweil and Lwin 2012a, b, Kurzweil 2013, Kurzweil and Lwin 2014, Aung et al 2017, Jin and Kyaw 2017, Koopowitz et al 2017, Yang et al 2017, Kurzweil and Ormerod 2018, Ding et al 2019, Kang et al 2019, Mu et al 2019, Ya et al 2019.…”
Section: Verification Of Species Occurrence and Taxonomic Statusmentioning
confidence: 99%
See 1 more Smart Citation